Design, Dimerization, and Recombinant Production of MCh-AMP1–Derived Peptide in Escherichia coli and Evaluation of Its Antifungal Activity and Cytotoxicity - Seyedjavadi, Sima Sadat; Khani, Soghra; Amani, Jafar; Halabian, Raheleh; Goudarzi, Mehdi; Hosseini, Hamideh Mahmoodzadeh; Eslamifar, Ali; Shams-Ghahfarokhi, Masoomeh; Imani Fooladi, Abbas Ali; Razzaghi-Abyaneh, Mehdi (Frontiers in Fungal Biology, 2021)
Fungal species resistant to current antifungal agents are considered as a serious threat to human health; the dilemma that has dragged attentions toward other sources of antifungals such as antimicrobial peptides (AMPs). In order to improve biological activity of a recently described antifungal peptide MCh-AMP1 from Matricaria chamomilla flowers, MCh-AMP1dimer (DiMCh-AMP1), containing 61 amino acid residues connected by flexible linker (GPDGSGPDESGPDES) was designed, expressed in Escherichia coli and its structure was analyzed using bioinformatics tools. DiMCh-AMP1 synthetic gene was cloned into pET-28a expression vector, which was then used to transform E. coli BL21 (DE3) strain. His-tag purification was achieved using metal-chelate affinity chromatography. Because there is no methionine residue in the DiMCh-AMP1 sequence, cyanogen bromide was successfully used to separate the target product from the tag. Reverse-phase high-performance liquid chromatography was used as the final step of purification. Results showed that recombinant peptide was produced in considerable amounts (0.9 mg/L) with improved antifungal activity toward both yeasts and moulds compared to its monomeric counterpart. The MIC and MFC values of DiMCh-AMP1 against Candida and Aspergillus species were reported in the range of 1.67 to 6.66 µM and 3.33 to 26.64 µM, respectively. Our results showed that while antifungal activity of dimerized peptide was improved considerably, its cytotoxicity was decreased implying that DiMCh-AMP1 could be a potential candidate to design an effective antifungal agent against pathogenic yeasts and moulds.